Evaluation of environmental impacts generated by the implementation and operation of an electrical substation: a case study in Palhoça, SC - Turmina, Eliana (2018)
Electricity is essential nowadays, but to reach agro-veterinary enterprises, as well as the final consumer, there is a need to implement projects that can impact the environment. As such, evaluating environmental impacts plays an important role, contributing to economic and social development allied to environmental factors. The objective of this study was to evaluate the impacts generated by an electrical substation, located in the municipality of Palhoça, state of Santa Catarina, by means of the Ad Hoc method, as well as of both matrices of interaction and attribute weighting. We analyzed the activities related to the implementation stages of the project consisting of earthworks when necessary and, later, civil construction activities. Finally, the operation stage of the enterprise consists of identifying the generating actions that are the activities of earthworks, leasing and construction of structures, excavations, drainage and grounding systems, electromechanical assemblies, personnel mobilization and substation maintenance and, consequently, environmental impacts. The activities conducted by the enterprise in question that can directly affect the environmental aspects such as: water, soil, atmospheric emissions, among others, besides social aspects. Using weighting and interaction matrices, it was possible to diagnose that most impacting activities occur in the implementation phase of the project. Most impacts, for the selected enterprise, were classified as of small importance, low magnitude and reversible. This case study may support future research and environmental studies in a variety of areas, depicting a method to demonstrate the importance and interaction of each impact, as well as presenting to licensing agencies an alternative method which may be required for future environmental impact studies.